DESAIN KONSEPTUAL DESA WISATA DI LAHAN NON-PRODUKTIF: UPAYA PENINGKATAN POTENSI LOKAL DESA GLAGAH, LAMONGAN - Dhiah Agustina Qahar (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
A tourist village is a village designated as a tourist attraction due to its unique appeal. A tourist village integrates attractions, accommodations, and supporting facilities. It is presented within a community structure that aligns with established customs and traditions. Glagah Village has an underutilized field, prompting the village head to propose a tourist village program to the field supervisor, who had previously surveyed the location. The intended tourist village aims to optimize the non-productive village field into a beneficial area for the community. Therefore, the 2024 UNISDA KKN team take the tasks to conceptualize and design the field to ensure its effective utilization for various village activities and events. The methods used in this community service program include site surveys, interviews with village officials, land use concept design using design software, and community socialization. The results indicate that the tourist village concept, incorporating the construction of a multipurpose hall, can enhance the functionality of the village field while fostering economic and social activities within the community. This project is expected to serve as a model for other villages seeking to optimize their underutilized land.